Empowering MSMEs through Corporate Social Responsibility Programs at PT Pertamina Marketing Operation Region in Indonesia: Advancing Sustainable Development Goal 8 - Lili Wardani Harahap; Rahmawati Rahmawati; Nurmadi Harsa Sumarta; Ari Kuncara Widagdo (Journal of Current Studies in SDGs, 2027)
Objective: To examine the role of the digital economy in empowering Micro, Small, and Medium Enterprises (MSMEs) and to identify the contribution of corporate social responsibility programs implemented by PT Pertamina Marketing Operation Region in supporting community economic empowerment and Sustainable Development Goal 8. Method: Qualitative approach using content analysis. Data were obtained from relevant literature, institutional documents, reports, and published information concerning the digital economy, MSME development, digital marketing, and corporate social responsibility programs. The data were classified, interpreted, and analyzed to identify the relationship between digital economic activities, community empowerment, and MSME development. Results: The findings show that sharing-economy business models and digital platforms, including Gojek, Traveloka, Tokopedia, and Bukalapak, contribute to Indonesia’s economic activities by expanding market access and creating new business opportunities. Social media is also widely used by millennials to exchange information and support digital marketing activities. Furthermore, PT Pertamina’s partnership-based CSR programs contribute to strengthening community economic activities and encouraging MSMEs to become more independent. Digital marketing training may enhance the information technology competencies of millennials and MSME actors while creating opportunities to generate income. Novelty: The study integrates the perspectives of the digital economy, MSME empowerment, and corporate social responsibility within a single framework and highlights their contribution to inclusive economic growth and the achievement of Sustainable Development Goal 8.